Residual solvent induced physical morphology and gas permeation in polyamide-imide membrane: Experimental investigation and molecular simulations. (15th February 2022) - Shiva Prasad, N.; Babarao, Ravichandar; Madapusi, Srinivasan; Sridhar, Sundergopal; Choudhury, Namita Roy; Bhargava, Suresh K.
Graphical abstract: Highlights: Compatibility of polymer–solvent assisted from HSP and Floury-Huggins parameters. Solvent with higher molar volume is favorable in creating an increased FFV. Atomistic simulations revealed the effect of residual solvent on CO2 and CH4 diffusion. Residual DMAc solvent affects transport properties positively. Good agreement between experimental and simulations was presented. Abstract: The present study focuses on understanding various residual solvent effects on the physical morphology and separation characteristics of polyamide-imide (Torlon) membranes. The dense membranes were indigenously synthesized by phase inversion technique using various solvents including, N, N-dimethyl formamide (DMF), N, N-dimethyl acetamide (DMAc) and N-methyl pyrrolidone (NMP) respectively. The effect of various solvents on the physical morphology and separation characteristics were studied using a combination of both experimental techniques and atomistic simulations. The Hansen solubility and Floury-Huggins parameters were used to understand the polymer–solvent interactions and further extended to correlated to separation characteristics. Scanning electron microscope (SEM) and atomic force microscopy (AFM) methods were used to investigate the resulted physical morphology of the membranes. Thermogravimetric analysis (TGA) and 1 H NMR spectra revealed residual solvent, hydrogen-bonding interactions with the Torlon polymer membrane. The experimental gas permeation studies demonstrated that the CO2 permeability in Torlon membranes follows the order T-NMP > T-DMAc > T-DMF. However, the membrane with the T-DMAc solvent exhibited higher ideal selectivity of 34.65 at 12.5 bar for CO2 /CH4 separation due to the lower diffusion coefficient of CH4 in the presence of residual DMAc. The predicted solubility and diffusion coefficients of CO2 and CH4 were shown to be in good agreement with the experimental results. Additionally, structural analysis of simulated models provided further insights into residual solvent effects on the microscopic properties and gas permeation. Overall, the Torlon membrane with the residual DMAc solvent showed positive effects on the transport properties and in turn enhance the diffusive selectivity.